EVALUATING TRAINING AND DEVELOPMENT PROGRAMS ON EMPLOYEE PERFORMANCE: A STUDY OF IMO STATE CIVIL SERVICE COMMISSION - Nehemiah Nwokorie, Chinedu (African Journal of Social and Behavioural Sciences, 2025)
This study evaluated the impact of training and development programs on employee performance in Imo State organisations, focusing specifically on the Imo State Civil Service Commission. It examined three critical dimensions of training effectiveness: training content relevance, frequency of training, and post-training support, and how each relates to task performance, productivity, and achievement of performance goals. A total of 311 respondents were selected using stratified random sampling, and data were collected through a structured four-point Likert scale questionnaire. The responses were analysed using Multivariate Analysis of Covariance (MANCOVA) in SPSS version 23. The findings revealed a statistically significant relationship between training content relevance and task performance, indicating that well- structured and job-relevant training enhances employee efficiency. Similarly, the frequency of training programs had a significant effect on productivity, affirming the value of regular and consistent training for civil servants. The demographic analysis indicated a balanced representation across age, gender, department, and years of service, enhancing the reliability of the results. Based on the findings, the study concluded that training and development are vital components for optimizing civil servant performance. It recommended the customization of training content, institutionalization of regular training schedules, and implementation of robust post-training support systems.